The effect of a running intervention on running ability and participation in children with cerebral palsy: a randomized controlled trial - Gibson, N.; Chappell, A.; Blackmore, A.; Morris, Susan; Williams, G.; Bear, N.; Allison, G. (Informa Healthcare, 2017)
Purpose: The purpose of this study is to evaluate effects of a running intervention on running ability and participation in children with cerebral palsy. Materials and method: Children with cerebral palsy (9–18 years) with Gross Motor Function Classification System levels I-III were randomly assigned to a 12-week running intervention or usual care. Primary outcomes included improvement in running ability (assessed by Goal Attainment Scaling, high level mobility (assessed by the High-Level Mobility Assessment Tool) and participation (assessed by the Participation and Environment Measure for Children and Youth). Secondary outcomes were aerobic and anaerobic fitness and agility. Blinded assessments took place at baseline and 12 weeks. Regression analysis adjusting for baseline differences was used to determine between group differences. Results: Forty-two participants (mean age 12.5 years, SD 2.8 years; 15 female) completed the study. Statistically significant group differences at 12-weeks were found for improvements in running ability (86% treatment group versus 0% control group achieved or exceeded their running goals, p < 0.001), and participation in the school environment (Participation and Environment Measure mean difference 1.18: 95%CI 1.00–1.39, p = 0.045). Conclusion: A 12-week individualized running training skills intervention results in achievement of running ability goals and participation in the school environment in children with cerebral palsy. • Implications for Rehabilitation • Children with cerebral palsy who can walk unaided demonstrate impairments in higher level mobility such as running. • Running is a motor skill that can be trained in children with cerebral palsy. • Individually tailored running skills intervention, delivered in a group context can improve goal-identified running ability and translate into a higher frequency of participation in school activities.